Моделювання та дослідження ефективності методу послідовного перегляду сторінок на web-сайті для різних законів розподілу ймовірностей звертання до сторінок - Юськів, Маркіян Ігорович; Цегелик, Григорій Григорович (НТУ "ХПІ", 2016)
Так як Інтернет – це набір сайтів та сторінок, все більш актуальним постає питання пошуку інформації на сторінках сайтів на основі заданих критеріїв. Розглянуто метод послідовного перегляду сторінок web-сайту. Знайдено математичне сподівання загального часу, необхідного для пошуку сторінки, для різних законів розподілу ймовірності звертання до сторінок. Визначено ефективність методу для різних законів розподілу ймовірності звертання до сторінки.

The object of this study is to review the organization and pages for given probabilities turning the pages. For performance criterion search page taken the expected total time required to find the page you want the user. One of the problem areas of the study is the behavior of the algorithm for different distribution laws. Therefore, further steps in the research was the model output for different laws of distribution and analysis of the results with existing data for these laws probability distribution page. For a given study introduced the concept of mathematical expectation of the time required to search for Web-page on the site and made it as a performance criterion. Input parameters are in such searching for viewing pages and reading pages that are constant parameters. Also, the input parameter is the number of pages on the site and this option is variable. The starting dependence parameter is the expectation of the time required to search for pages on the site by changing the number of pages for different laws probability distribution pages. As a result of working formulas for the expectation of the time required to find information on a page based on parameters that are taken into account in a consistent finding information on the page. With the efficiency criterion adopted by the expectation of the time required to search for pages on the Web-site method consistent browsing. Expressions for the expectation that depend on different laws probability distribution pages. The comparative analysis of the effectiveness of the method, different laws probability distribution pages. Depending calculated mathematical expectation of the time required to search for pages on the site, on changes in the law probability distribution pages for a given number of pages.
Modelling and investigation of efficiency of consecutive revision method for browsing of pages on a web-site for different distribution laws of probability of accessing pages
Keywords: моделювання доступу; послідовно організовані сторінки; закони розподілу ймовірностей; REST-сервіси; розпаралелювання пошуку; modeling access; consistently organized pages; laws of probability distribution; REST-services; paralleling the search